Property, freedom and money: Modern Capitalism reassessed - Domenech Figueras, Antoni (2016)
Large exchange markets, big money, interest-bearing credit, big landholdings, proletarian masses, imperial expansion and even ‘capital’ or ‘salaried workers’, are not in themselves specific, unique institutional features of Modern Capitalism. This article argues that the features that characterize Modern Capitalism are a massive emergence of ‘free’, monetized wage labour, a self-propelled rush to unbounded world expansion and the progressive conversion of expropriated and privatized land into a monetized commodity, as well as a radically new use of the ancestral social institutions of money and credit as an instrument for financing the production of commodities to obtain a surplus in the form of monetary profit, but also to generate expropriatory social debt relations. This article explains these dynamic historical forces and their importance for political philosophy and for legal and economic history and economics and sheds some light on the relationship between ‘capitalism’ and ‘modernity’.